2013
DOI: 10.1063/1.4831672
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of field emission properties of α-Fe2O3 nanoflakes due to the lowered back contact barrier after high energy X-ray irradiation

Abstract: Improvement in the field emission properties of α-Fe2O3 nanoflakes is observed after high energy X-ray irradiation from synchrotron radiation. Field emission threshold field of α-Fe2O3 nanoflakes is found to decrease from 10.1 to 7.8 MV/m after X-ray irradiation with the dose of 9.0 × 1014 phs/cm2. Electrical measurement reveals that the potential barrier at the back contact between the α-Fe2O3 layer and the iron substrate changes after X-ray irradiation. The observed threshold field decrease is well explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…nanowires/leaves which have grown on an underlying layer of Fe 3 O 4 . The latter is located between the Fe substrate and the outer coverage of nanowires/leaves, as also reported in similar earlier studies [39,40].…”
Section: Figsupporting
confidence: 85%
See 1 more Smart Citation
“…nanowires/leaves which have grown on an underlying layer of Fe 3 O 4 . The latter is located between the Fe substrate and the outer coverage of nanowires/leaves, as also reported in similar earlier studies [39,40].…”
Section: Figsupporting
confidence: 85%
“…In this regard, the charge carriers (i.e., Li + and e -) could not migrate immediately through the whole anisotropic structures and the newly formed phases upon ongoing conversion.It should be mentioned here that the contact resistance of these iron oxide structures at the interface with the substrate could play a significant role, since the electrode contacts can have a greater influence than commonly thought[54]. Indeed, some previous I-V measurements of an analogous system based on α-Fe 2 O 3 nanoflakes grown on Fe by thermal oxidation[39] indicate that a Schottky barrier exists at the underlying interface and that the electrical contact of these oxide structures behaves in a non-ohmic way at low applied voltages. This subtle aspect is often neglected in electrochemical studies, where the intimate contact of a metal/semiconductor interface is tacitly assumed to account for a reasonable electrical conduction, especially when the metal represent the current collector.…”
mentioning
confidence: 93%
“…Determining how the high-energy X-ray irradiation affects the crystalline structure and field electron emission properties of tungsten oxide nanomaterials is an important issue for practical application. However, there has been little research on this important issue, 30–32 which still remains an open question. In this paper, W 18 O 49 nanowires were prepared by thermal evaporation and then irradiated by high-energy X-rays.…”
Section: Introductionmentioning
confidence: 99%
“…Using the thermal oxidation method, vertically aligned α-Fe 2 O 3 nanomaterials can be grown directly on substrates [24], which is essential for their application as field emitters. The field emission properties of α-Fe 2 O 3 nanomaterials have been studied [25][26][27][28][29][30][31][32]. Sow reported the field emission properties of α-Fe 2 O 3 nanoflakes in 2005, which were prepared on an atomic force microscope tip and showed a high current density of 1.6 A cm −2 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ar plasma treatment can clean nanoflakes, create ultra sharp sub-tips, and significantly enhance electron emission [27]. In our previous report, we found that the field emission properties of α-Fe 2 O 3 nanoflakes could be enhanced by in situ thermal treatment [30] or with an appropriate dose of high energy x-ray irradiation [31]. However, the above method is a little complicated and always requires some special devices.…”
Section: Introductionmentioning
confidence: 99%